Expression of Plxdc2/TEM7R in the developing nervous system of the mouse. - MITCHELL, KEVIN (My University, 2007)
Plexin-domain containing 2 (Plxdc2) is a relatively uncharacterised transmembrane protein with an area of nidogen homology and a plexin repeat (PSI domain) in its extracellular region. Here, we describe Plxdc2 expression in the embryonic mouse, with particular emphasis on the developing central nervous system. Using light microscopy and optical projection tomography (OPT), we analyse RNA in situ hybridization patterns and expression of two reporter genes, -geo (a fusion of -galactosidase to neomycin phosphotransferase) and placental alkaline phosphatase (PLAP) in a Plxdc2 gene trap mouse line (KST37; [Leighton, P.A., Mitchell, K.J., Goodrich, L.V., Lu, X., Pinson, K., Scherz, P., Skarnes, W.C., Tessier-Lavigne, M., 2001. DeWning brain wiring patterns and mechanisms through gene trapping in mice. Nature 410, 174?179]). At mid-embryonic stages (E9.5?E11.5) Plxdc2- geo expression is prominent in a number of patterning centres of the brain, including the cortical hem, midbrain?hindbrain boundary and the midbrain Xoorplate. Plxdc2 is expressed in other tissues, most notably the limbs, lung buds and developing heart, as well as the spinal cord and dorsal root ganglia. At E15.5, expression is apparent in a large number of discrete nuclei and structures throughout the brain, including the glial wedge and derivatives of the cortical hem. Plxdc2- geo expression is particularly strong in the developing Purkinje cell layer, especially in the posterior half of the cerebellum. The PLAP marker is expressed in a number of axonal tracts, including the posterior commissure, mammillotegmental tract and cerebellar peduncle. We compare Plxdc2- geo expression in the embryonic brain with the much more restricted expression of the related gene Plxdc1 and with members of the Wnt family (Wnt3a, Wnt5a and Wnt8b) that show a striking overlap with Plxdc2 expression in certain areas
PUBLISHED
Keywords: Genetics; Plexin-domain containing 2 (Plxdc2)